Manusia Dalam Logika Politik di Era Media Digital - Prasetyono, Emanuel; Pandor, Pius (Litbang STFT Widya Sasana Malang, 2024)
Political praxis in the digital media era often contains biases in understanding human dignity. This article wants to investigate whether the political logic in such an era contains certain concepts about humans that are implicit, hidden, or intentionally hidden. The theoretical framework of Shoshana Zuboff and Agus Sudibyo's thoughts on